Architecture Design and Catalytic Activity: Non‐Noble Bimetallic CoFe/fe3O4 Core–Shell Structures for CO2 Hydrogenation. Issue 5 (18th December 2022) - Miao, Wenkang; Hao, Ronghui; Wang, Jingzhou; Wang, Zihan; Lin, Wenxin; Liu, Heguang; Feng, Zhenjie; Lyu, Yingchun; Li, Qianqian; Jia, Dongling; Ouyang, Runhai; Cheng, Jipeng; et al.
Abstract: Non‐noble metal catalysts now play a key role in promoting efficiently and economically catalytic reduction of CO2 into clean energy, which is an important strategy to ameliorate global warming and resource shortage issues. Here, a non‐noble bimetallic catalyst of CoFe/Fe3 O4 nanoparticles is successfully designed with a core–shell structure that is well dispersed on the defect‐rich carbon substrate for the hydrogenation of CO2 under mild conditions. The catalysts exhibit a high CO2 conversion activity with the rate of 30% and CO selectivity of 99%, and extremely robust stability without performance decay over 90 h in the reverse water gas shift reaction process. Notably, it is found that the reversible exsolution/dissolution of cobalt in the Fe3 O4 shell will lead to a dynamic and reversible deactivation/regeneration of the catalysts, accompanying by shell thickness breathing during the repeated cycles, via atomic structure study of the catalysts at different reaction stages. Combined with density functional theory calculations, the catalytic activity reversible regeneration mechanism is proposed. This work reveals the structure–property relationship for rational structure design of the advanced non‐noble metallic catalyst materials with much improved performance. Abstract : A reversible deactivation/regeneration of the catalytic activity is found in non‐noble bimetallic CoFe/Fe3 O4 core–shell structures, used for CO2 hydrogenation with promoted performance by rational structure design. Such phenomenon results from the oxide shell "breathing" induced by cobalt reversible exsolution/dissolution in the shell during the cycling reaction.